(untitled) (Ameghiniana, 2013)
Fossil plants from the Pampa de Agnía Croup, from northern Chubut province, Patagonia, are described. Coniopteris meschiana, Otozamites chubutensis and O. sueroi are proposed as new species: worid-wíde distributed species as Sagenopteris rhoijoha, Otozamites hisloni and Ginkgoites ef. digitata (this last being the first cíted Ginkgoal from Argentine Liassic strata ) are also found, together with Scleropteris vincei and Otozamites ulbosaxatiiis, prevíously known from other Argentine Liassic sediments. The Pampa de Agnia Croup is composed of three formations: F. C